ANALISIS DAMPAK TEKNOOGI BUDIDAYA JAGUNG TERHADAP TINGKAT PENDAPATAN DAN DISTRIBUSI PENDAPATAN PETANI JAGUNG PADA KAWASAN USAHA AGRIBISNIS TERPADU (KUAT) DI RASAU JAYA KOMPLEK - Adi Suyatno, Nur Fajar Febtysiana, Erlinda Yurisinthae, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2014)
The purpose of the study is (1) To determine the impact of maize cultivation technology to the level of income of corn farmers who use technology ( adopter ) and that do not use ( non- adopters ). (2) To determine the impact of maize cultivation technology on income distribution of farmers who are using technology ( adopter ) and which does not use the ( non- adopters ). Sampling is done by simple random sampling method in each category maisng adopter and non- adopter . The analytical tools used in this research is the analysis of different test t Calculate Income and Income Distribution Analysis by the Gini coefficient based on ( Gini Ratio ) , and Lorenz curve. The results showed that the overall average cash income of farmers are using the technology of cultivation ( adopter ) is greater than the average cash income of farmers who do not use the technology of cultivation ( non- adopters ) . From the statistical result obtained t value less than or equal to t table ( t ≤ t hits the table ) at the db = n1 + n2 – 2. This suggests that the income level of farmers are using the technology of cultivation ( adopter ) did not differ from the level of income of farmers who do not use the technology of cultivation ( non- adopters ) . Criteria based on the Gini coefficient ( Gini Ratio ) , the Lorenz curve and indicates if the distribution of the income of farmers who do not use corn cultivation technology ( non- adopters ) is more evenly distributed than the income of farmers who do not use the technology of cultivation ( non- adopters ) . This suggests that the impact on the use of technology in higher levels of inequality . Keywords : Technology Impact , Income , Income Distribution , Region Agribusiness integrated